PENGARUH CELEBRITY ENDORSEMENT, CITRA MEREK, KEPERCAYAAN TERHADAP MINAT BELI KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA SOMAYA SKINCARE KOSMETIK DI SITUBONDO - Mala, Yunita Kadi; Widaninggar, Nanda; Rachman, Riza (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Somaya is a cosmetic or beauty shop, located in Situbondo Regency, has become a comfortable skincare and make-up center not only for teenagers but also for adults. Somaya provides a variety of the most complete products and is very viral on social media. Somaya cosmetic shop is the secret dream of a clean, clear, glowing face for women to appear healthier, safer and already has a permit from the Food and Drug Supervisory Agency (BPOM). The purpose of this study was to analyze the Influence of Celebrity Endorsement, Brand Image, Trust on Consumer Purchase Interest with Consumer Satisfaction as an Intervening Variable on Somaya Skincare Cosmetics in Situbondo. The number of samples used in this study was 96 respondents of Somaya Skincare cosmetics in Situbondo. The sampling technique was determined by simple random sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, showed that Celebrity endorsement has a significant positive effect on Consumer Satisfaction, Brand image has a negative but insignificant effect on Consumer Satisfaction, Trust has a significant positive effect on Consumer Satisfaction, Celebrity endorsement has a positive but insignificant effect on Purchase Intention, Brand image has a negative but insignificant effect on Purchase Intention, Trust has a positive but insignificant effect on Purchase Intention, Consumer satisfaction has a significant positive effect on Purchase Intention, Celebrity endorsement has a positive but insignificant effect on Purchase Intention through Consumer Satisfaction, Brand image has a negative but insignificant effect on Purchase Intention through Consumer Satisfaction, Trust has a significant positive effect on Purchase Intention through Consumer Satisfaction. Keywords: Celebrity Endorsement, Brand Image, Trust, Purchase Intention, and Consumer Satisfaction.